Linguistic landscape [ expanding the scenery - Gorter, D. [ (Durk)]; Shohamy, Elana Goldberg (Routledge, 2009)
Proposes to offer a resource to students and researchers in the field of Applied Linguistics on the topic of the linguistic landscape. This book refers to the signs, directions, and other documentation that appear in the public space, and includes the interpretation of this 'visible language' in social, political, and economic contexts